Development of Torrance Test Creative Thinking Verbal (TTCT-V) Instrument for Measuring Arabic Creative Writing - Arifa, Zakiyah; Sari, Risna Rianti; Fatim, Al Lastu Nurul; Hilmi, Danial; Anis, Muhammad Yunus; Setiyadi, Alif Cahya (Arabi : Journal of Arabic Studies, 2023)
This research aims to develop a TTCT-Verbal instrument to measure students' creative thinking skills and Arabic creative writing that essential competence of 21st-century skills. The instrument was developed based on Torrance's (1970) verbal test indicators and al-Bari’s Arabic creative writing (2009). The RD method used the 4D model design of Thiaragajan (1974). The instrument was developed with 6 components of creative thinking: ask and guess, guessing causes, guessing consequences, product improvement activity, unusual use activity, and suppose activity, with 5 items covering descriptive writing, news, poetry, Arabic quotes, and short stories. Based on the results of the 3 experts' validation tests showed that the TTCT-Verbal instrument was very valid, with an average of 4.5, and then tested on 30 university students. The results of the instrument validity test showed that all items were valid, and the reliability test showed reliable results. Therefore, this instrument is suitable for measuring the level of creative thinking and Arabic creative writing.